1998
DOI: 10.1111/j.1439-0523.1998.tb01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications and impact of molecular markers on evolutionary and diversity studies in the genus Allium

Abstract: Allium is a large variable genus containing %700 species, among them the economically important crops bulb onion, garlic and leek and many other crop species of minor or local importance. As the methods became available and more refined, systematic studies using biochemical and molecular markers were published to complement and offset the growing amount of data based on morphological, anatomical and other traditional approaches. Using isozymes and later restriction fragment length polymorphisms (RFLPs) and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…Isozymes analysis is more reliable than traditional methods since the expression of isozymes loci are co-dominant, in addition this technique provides a fairly rapid and inexpensive alternative tool for taxonomic studies and for identifying fungi species (Ryan and Scowcroft, 1987;Bonde et al, 1993;Bragaloni et al, 1997). Klaas (1998) reported that the isozyme markers can correctly identify several levels of taxa, accessions, and individuals, since the assumption of homology can be more accurate than for some genomic DNA markers.…”
Section: T Mentagrophytes (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Isozymes analysis is more reliable than traditional methods since the expression of isozymes loci are co-dominant, in addition this technique provides a fairly rapid and inexpensive alternative tool for taxonomic studies and for identifying fungi species (Ryan and Scowcroft, 1987;Bonde et al, 1993;Bragaloni et al, 1997). Klaas (1998) reported that the isozyme markers can correctly identify several levels of taxa, accessions, and individuals, since the assumption of homology can be more accurate than for some genomic DNA markers.…”
Section: T Mentagrophytes (E)mentioning
confidence: 99%
“…Isozyme term means "the different molecular forms in which which proteins may exist with the same enzymatic specificity" (Markert and Moller, 1959). Klaas (1998) reported that the isozyme markers can correctly identify several levels of taxa, accessions, and individuals, since the assumption of homology can be more accurate than for some genomic DNA markers. Siddiquee et al (2010) used eight enzymes and single protein pattern systems to identify and study the genetic relationships among 27 isolates of Trichoderma harzianum, 10 isolates of Trichophyton aureoviride, and 10 isolates of Trichophyton longibrachiatum from Southern Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…cyaneum was the shortest (635 bp) and A. victorialis the longest (646 bp) among the investigated Korean taxa. The three morphologically similar taxa, A. thunbergii, A. sacculiferum that has been included in A. thunbergii, and A. deltoide-Jistulosum, had the same ITS lengths of 641 bp, but were clearly distinguished in the phylogenetic analysis of their ITS sequences.Allium L. (Alliaceae) contains about 700-750 taxa in northern temperate region, including a number of important edible plants such as onion, green onion, garlic, leek and wild garlic (Hanek et al, 1992;Berg et al 1996;Mes et al, 1997;Klaas, 1998). The genus is characterized by perennials with alliaceous ordour and tunicated bulb.…”
mentioning
confidence: 99%
“…Allium L. (Alliaceae) contains about 700-750 taxa in northern temperate region, including a number of important edible plants such as onion, green onion, garlic, leek and wild garlic (Hanek et al, 1992;Berg et al 1996;Mes et al, 1997;Klaas, 1998). The genus is characterized by perennials with alliaceous ordour and tunicated bulb.…”
mentioning
confidence: 99%
See 1 more Smart Citation